Equine pituitary pars intermedia dysfunction: current understanding and recommendations from the Australian and New Zealand Equine Endocrine Group. Issue 7 (3rd June 2018) - Secombe, CJ; Bailey, SR; de Laat, MA; Hughes, KJ; Stewart, AJ; Sonis, JM; Tan, RHH
Abstract : The purpose of this article is to provide a review of the current knowledge and opinions about the epidemiology, clinical findings (including sequelae), diagnosis, treatment and monitoring of equine pituitary pars intermedia dysfunction, particularly in the Australian context. This information and the recommendations provided will assist practitioners in making informed decisions regarding the diagnosis and management of this disorder.